Implementing Curriculum Management of the Productive Teacher Working Group A Case Study at SMK Negeri 2 Palopo - Mulya Akbar; Salmilah Salmilah; Muhaemin Muhaemin (International Journal of Educational Administration, Management, and Leadership, 2024)
This study examines the management of the Musyawarah Guru Mata Pelajaran (MGMP), or Subject Teacher Working Group, for productive teachers in implementing the Independent Curriculum at SMK Negeri 2 Palopo. The objectives are to describe the structure and mechanisms of MGMP, identify supporting and inhibiting factors, and develop strategies to improve its effectiveness. Using a qualitative case study approach, data were collected through interviews, observations, and documentation, and analyzed using G.R. Terry’s management theory and principles of Islamic educational management. The findings show that MGMP management is relatively effective through functions such as planning, organizing, actuating, and controlling. Supporting factors include school support, teacher commitment, coordination, and involvement of business and industry, while inhibiting factors consist of limited teacher availability, heavy teaching loads, changing learning outcomes, and inadequate facilities and training. Improvement strategies involve flexible scheduling, digital forums, crossschool collaboration, teacher capacity building, and policy support. This research emphasizes that the success of MGMP depends not only on formal management effectiveness but also on values like syūrā (deliberation), ta‘āwun (collaboration), and itqān (professionalism).